How green trust, consumer brand engagement and green word-of-mouth mediate purchasing intentions - Guerreiro, J.; Pacheco, M. (Sustainability, 2021)
An increasing interest in environmental problems around the world has significantly expanded the demand for green goods, transforming green marketing into an effective tool for businesses to achieve competitive advantage. Yet, as more firms become aware of this strategic advantage, greenwashing activities can also flourish, and customers grow more cautious about green efforts by firms. The present research examines how greenwashing expectations of customers affect their green buying decisions by studying how green trust, consumer brand engagement and green word-of-mouth mediate this relationship. A total of 302 subjects participated in a survey to study greenwashing effects using a high involvement green ad and a low involvement green ad. Results were analyzed using a PLS-SEM approach. The findings show that the greenwashing expectations of customers have no direct effect on green purchase decisions, but that green trust and green word-of-mouth mediate this relationship. Likewise, greenwashing perception significantly affects customer brand engagement indirectly through green trust and there is a full mediation between greenwashing perception and green purchasing intention through green trust, customer brand engagement and green word of mouth. Therefore, the study shows that having a low perception of greenwashing is not enough to increase purchases. For that to occur, companies need to ensure that WOM communicates such efforts and that consumers trust these green initiatives.